Design and Synthesis of Chiral Spiro Ligands - Bajracharya, Gan B. (Journal of Nepal Chemical Society, 2013)
Tremendous progress has been made in design and synthesis of chiral spiro ligands and researches in finding their utility have led development of several asymmetric- and organo-catalysis. This review describes recent advances in synthesis of chiral spiro ligands. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8036 Journal of Nepal Chemical Society Vol.28, 2011 1-23 Uploaded date: May 6, 2013